Evaluación del ruido y su incidencia en la salud laboral en el área del molino 5 de la empresa productos familia Sancela del Ecuador en el período 2015 - 2016 - Achig Cabrera, Rafael Antonio (2016)
The risk factor noise at the enterprise level is considered one of the main drawbacks to those exposed workers and it directly affects their occupational health, is why during the course of this investigation it was found that "Productos Familia Sancela del Ecuador SA" Company in the area of the mill 5 several of employees directly and indirectly involved in the production process already have hearing loss, they may have a work origen or not work complementary to the level of noise exposure in their different work stations....